Citizenship policies in the New Europe - Bauböck, Rainer; Perchinig, Bernhard, 1958-; Sievers, Wiebke (IMISCOE research., 2009)
The two most recent EU enlargements in May 2004 and in January 2007 have greatly increased the diversity of historic experiences and contemporary conceptions of statehood, nation-building and citizenship within the Union. How did newly formed states determine who would become their citizens? How do countries relate to their large emigrant communities, to ethnic kin minorities in neighbouring countries and to minorities in their own territory? And to which extent have their citizenship policies been affected by new immigration and integration into the European Union? Citizenship Policies in the.